2022
DOI: 10.1364/optcon.457642
|View full text |Cite
|
Sign up to set email alerts
|

Nodeless antiresonant hollow core fiber for low loss flatband THz guidance

Abstract: This paper reveals a THz leading nodeless antiresonant slotted hollow core fiber (NARS-HCF) with low transmission loss and broad band flat near zero dispersion. We have achieved better results in a simpler structure as far as we know: a minimal confinement loss in the order of around 10−4 dBm-1 and a very low effective material loss of 0.0248 dBm-1, resulting in a lowest total transmission loss of 0.0254 dBm-1 at 1.27 THz and offering a 0.88 THz (0.8 THz – 1.68 THz) low loss transmission bandwidth with the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The spectral region centered at 5.4 μm is important for the CO laser, an alternative light source in the mid-IR region for material processing and spectroscopy [17]. Various NCF structures such as tubular [11], elliptical [18,19,34], lotus-shaped [35], conjoined-tube [36], double-ring [37], adjacent nested [38], nested compounded [39], double nested [40,41], and bar supported NCFs [41][42][43][44] have been reported to improve the transmission losses of hollow-core structures. Although several studies on bar-supported structures have been reported, they are mainly focused on light guidance in either the near-IR or terahertz (THz) regions.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral region centered at 5.4 μm is important for the CO laser, an alternative light source in the mid-IR region for material processing and spectroscopy [17]. Various NCF structures such as tubular [11], elliptical [18,19,34], lotus-shaped [35], conjoined-tube [36], double-ring [37], adjacent nested [38], nested compounded [39], double nested [40,41], and bar supported NCFs [41][42][43][44] have been reported to improve the transmission losses of hollow-core structures. Although several studies on bar-supported structures have been reported, they are mainly focused on light guidance in either the near-IR or terahertz (THz) regions.…”
Section: Introductionmentioning
confidence: 99%